Immobilization of maize tassel in polyvinyl alcohol for the removal of phosphoric compounds from surface water near farmland. Issue 1 (1st January 2021) - Yahya, Muibat Diekola; Agie, Jennifer Osato; Obayomi, Kehinde Shola; Olugbenga, Adeola Grace; Afolabi, Eyitayo Amos
Abstract: In this study, proximate analysis and characterization techniques were carried out on maize tassel fibers immobilized with Polyvinyl Alcohol (PVA) for its usability as a biosorbent for adsorption process. The surface chemistry of the biomaterial showed the presence of carboxylic groups and lactone groups, and this was confirmed by the Fourier Transform Infrared spectroscopy. The Boehm titration also showed the number of acidic sites as 0.9 mmol/g, in the material. The proximate analysis revealed the moisture content, ash content, apparent density, and particle size to be 4.51%, 2.13%, 0.41 g/mL, and 300 μm, respectively. The Brunauer–Emmett–Teller (BET) analysis revealed the surface area, pore-volume, and size to be 652.3 m 2 /g, 0.4056 cm 3 /g, and 2.144 nm, respectively. The tassel was added to the polyvinyl alcohol at a temperature of 80°C with the aid of a magnetic stirrer in the ratio of 2:1, after which it was cooled and extruded with the aid of a syringe to form beads. The column efficiency performance of the biosorbent was carried out by varying flow rates, bed heights, and initial metal ions concentrations on the breakthrough curve to get the breakthrough and exhaustion time needed by the biosorbent. The column kinetics was subjected to Clark and Thomas isotherms. The Thomas model predicted the breakthrough better than the Clark model for the phosphoric compounds with an R 2 value of 97.5% for bed heights and flow rates and lower error function.